Kandungan impor dan daya saing internasional barang-barang berteknologi tinggi - Munrokhim Misanam (Economic Journal of Emerging Markets, 2000)
One important factor determining international trade is technology content of each product. The goal of this research is to examine whether Indonesia has ability to export product having high technology content.